2019
DOI: 10.1083/jcb.201901077
|View full text |Cite
|
Sign up to set email alerts
|

Cell and tissue morphology determine actin-dependent nuclear migration mechanisms in neuroepithelia

Abstract: Correct nuclear position is crucial for cellular function and tissue development. Depending on cell context, however, the cytoskeletal elements responsible for nuclear positioning vary. While these cytoskeletal mechanisms have been intensely studied in single cells, how nuclear positioning is linked to tissue morphology is less clear. Here, we compare apical nuclear positioning in zebrafish neuroepithelia. We find that kinetics and actin-dependent mechanisms of nuclear positioning vary in tissues of different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 67 publications
6
49
0
Order By: Relevance
“…(Bergert et al, 2015;Liu et al, 2015;Ruprecht et al, 2015). Similarly, neuroepithelial cells alter the subcellular distribution of actomyosin and adopt different force mechanisms during nuclear translocation depending on cell shape and tissue morphology (Yanakieva et al, 2019). It is thus possible that neurons might also adopt differential cytoskeletal dynamics depending on the extracellular mechanical environment.…”
Section: Actin-myosin Based Nuclear Translocationmentioning
confidence: 99%
“…(Bergert et al, 2015;Liu et al, 2015;Ruprecht et al, 2015). Similarly, neuroepithelial cells alter the subcellular distribution of actomyosin and adopt different force mechanisms during nuclear translocation depending on cell shape and tissue morphology (Yanakieva et al, 2019). It is thus possible that neurons might also adopt differential cytoskeletal dynamics depending on the extracellular mechanical environment.…”
Section: Actin-myosin Based Nuclear Translocationmentioning
confidence: 99%
“…Actin cables are utilized in other contexts, but in those cases nuclei are coupled to the actin cables used as tracks for nuclear transport (Folker et al, 2011;Luxton et al, 2010;Luxton et al, 2011). The retinal neuroepithelium in fish utilizes a different sort of formindependent actin network to push the nucleus apically, and cortex-anchored and bundled actin modulated by myosin may generate the pushing force (Yanakieva et al, 2019). Microtubule dependent pushing and pulling forces are also widely used to move nuclei (Adames and Cooper, 2000;Gönczy et al, 1999;Levy and Holzbaur, 2008;Tran et al, 2001;Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that nuclei in the hindbrain start migrating from variable apicobasal positions and move toward the apical surface in a directed and smooth manner, and this movement is controlled by Rho-ROCK-dependent myosin contractility [27]. However, the mechanisms by which actin generates the forces required for apical nuclear movement and the link between forces and atoh1b are not understood.…”
Section: Discussionmentioning
confidence: 99%